2010
DOI: 10.1152/ajpregu.00278.2010
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of gastric contractions and circadian gastric motility in the free-moving conscious house musk shrew (Suncus murinus)

Abstract: Physiological characteristics of gastric contractions and circadian gastric motility in the free-moving conscious house musk shrew (Suncus murinus). Am J Physiol Regul Integr Comp Physiol 299: R1106 -R1113, 2010. First published August 4, 2010 doi:10.1152/ajpregu.00278.2010.-Although many studies have demonstrated the physiological action of motilin on the migrating motor complex, the precise mechanisms remain obscure. To obtain new insights into the mechanisms, we focused on the house musk shrew (Suncus mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 43 publications
10
49
0
Order By: Relevance
“…From in vivo and in vitro experiments using S. murinus, we demonstrated that motilin-induced gastric contractions are mediated through the myenteric plexus (Mondal et al 2011;Sakahara et al 2010). Similar results have been reported in other species (De Smet et al 2009;Kitazawa et al 1995;Mizumoto et al 1993;Ohshiro et al 2008;Van Assche et al 1997).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…From in vivo and in vitro experiments using S. murinus, we demonstrated that motilin-induced gastric contractions are mediated through the myenteric plexus (Mondal et al 2011;Sakahara et al 2010). Similar results have been reported in other species (De Smet et al 2009;Kitazawa et al 1995;Mizumoto et al 1993;Ohshiro et al 2008;Van Assche et al 1997).…”
Section: Introductionsupporting
confidence: 85%
“…Previously, we determined cDNA sequences of S. murinus motilin and ghrelin using PCR cloning (Ishida et al 2009;Tsutsui et al 2009). We then studied the contractile properties of the S. murinus stomach, in both conscious free-moving S. murinus and in an organ bath experiment, and found that S. murinus has almost the same GI motility and motilin response as that found in humans and dogs (Sakahara et al 2010;Tsutsui et al 2009), indicating that S. murinus can be used for GI motility studies. Moreover, many studies have been performed to identify the rodent motilin gene, no convincing results of sequencing have been reported so far.…”
Section: Introductionmentioning
confidence: 92%
“…During the fasted state, the suncus stomach and duodenum showed clear migrating phase III contractions (intervals of 80-150 min) as found in humans and dogs, and motilin injection also increased the gastric motility index in a dose-dependent manner (Sakahara, et al 2010). Moreover, pretreatment with atropine completely abolished the motilin-induced gastric phase III contractions (Sakahara et al 2010). Since suncus has almost the same GI motility and motilin response as those found in humans and dogs, suncus would be a suitable model to analyze the interaction of motilin and ghrelin in gastric motility.…”
Section: Roles Of Motilin and Ghrelin In Gastric Motilitysupporting
confidence: 53%
“…Administration of suncus motilin showed almost the same contractile effect as that of human motilin in vitro ). During the fasted state, the suncus stomach and duodenum showed clear migrating phase III contractions (intervals of 80-150 min) as found in humans and dogs, and motilin injection also increased the gastric motility index in a dose-dependent manner (Sakahara, et al 2010). Moreover, pretreatment with atropine completely abolished the motilin-induced gastric phase III contractions (Sakahara et al 2010).…”
Section: Roles Of Motilin and Ghrelin In Gastric Motilitymentioning
confidence: 82%
“…Previous studies demonstrated that gastric contractions are strongly associated with plasma motilin levels and that gastric phase III-like contractions were induced by the intravenous administration of motilin in humans [7], dogs [8,9], and suncus [10,11].…”
Section: Introductionmentioning
confidence: 99%